The Extraction of β-Carotene from Microalgae for Testing Their Health Benefits - Jing Wang; Xinge Hu; Junbin Chen; Tiannan Wang; Xianju Huang; Guoxun Chen (Foods, 2022)
β-carotene, a member of the carotenoid family, is a provitamin A, and can be converted into vitamin A (retinol), which plays essential roles in the regulation of physiological functions in animal bodies. Microalgae synthesize a variety of carotenoids including β-carotene and are a rich source of natural β-carotene. This has attracted the attention of researchers in academia and the biotech industry. Methods to enrich or purify β-carotene from microalgae have been investigated, and experiments to understand the biological functions of microalgae products containing β-carotene have been conducted. To better understand the use of microalgae to produce β-carotene and other carotenoids, we have searched PubMed in August 2021 for the recent studies that are focused on microalgae carotenoid content, the extraction methods to produce β-carotene from microalgae, and the bioactivities of β-carotene from microalgae. Articles published in peer-reviewed scientific journals were identified, screened, and summarized here. So far, various types and amounts of carotenoids have been identified and extracted in different types of microalgae. Diverse methods have been developed overtime to extract β-carotene efficiently and practically from microalgae for mass production. It appears that methods have been developed to simplify the steps and extract β-carotene directly and efficiently. Multiple studies have shown that extracts or whole organism of microalgae containing β-carotene have activities to promote lifespan in lab animals and reduce oxidative stress in culture cells, etc. Nevertheless, more studies are warranted to study the health benefits and functional mechanisms of β-carotene in these microalgae extracts, which may benefit human and animal health in the future.